(untitled) (Journal of Social Sciences Review, 2023)
The current study deals with the comparison of three variables among working officials, i.e. work-family conflict with psychological well-being and the quality of life of the employees. The participants of this study were officials belonging to different fields of life, such as doctors, teachers, lawyers and bankers. The sample of this study was (N=20) individuals screened out with higher levels of work-family conflicts out of the sample of (N=100) officials. Data was collected by using three scales. The level of work-family conflict was checked by administering WFC-Scale developed by Haslam et al. (2015). The level of psychological well-being was measured by using Psychological Well-being Scale developed by Ryff (1995), and the level of Quality of Life was measured by using the Quality of Life scale developed by WHO (1998). The collected data was analyzed by SPSS. The statistical analysis of the data showed that the overall level of WFC was higher among females as compared to male working officials. The quality of life was higher among males as compared with female working officials. The comparison also showed that the WFC was higher among unmarried officials, and the PW & QL was higher among married officials. Hence, the study concluded that female officials are suffering from more WFC instead of males.